Processamento auditivo central e potenciais evocados auditivos em idosos: um estudo de referências - Peixe, Bruna Pias (2018)
Considering the growth of the elderly population at the national and world level, this study sought to generate reference values for different central auditory processing tests, investigating the influence of peripheral hearing and considering schooling and cognition in this population. It also aimed to study the performance difference between the ears in the Brainstem Auditory Evoked Potential (BAEP) with click stimulus, as well as to generate reference values for Frequency-Following Response with speech stimulus (FFR-speech). This research was prospective, quantitative and transversal. All elderly subjects underwent anamnesis, meatoscopy, pure tone audiometry, logoaudiometry, imitanciometry, Edinburgh Manual Dominance Test, Mini Mental State Examination (MMSE), Dichotic Digit Testing (DDT), Dichotic Sentence Identification Test (DSI), Masking Level Difference (MLD), Adapted Compressed Speech Test (ACS), Standard Frequency Test (SFT), Standard Duration Test (SDT), Random Gap Detection Test (RGDT), BAEP-click and FFR-speech. Due to the strict eligibility criteria, the sample consisted of 43 elderly individuals, aged between 60 and 81 years old, mean of 66.6 years, being 14 male and 29 female. Regarding the audiological characteristics, the elderly were included with normal hearing thresholds and light and moderate sensorineural hearing loss classified by the World Health Organization. In addition to the possibility of generating reference values, the results indicated that, in the right ear, the higher the degree of hearing loss, the worse the MMSE scores, and the lower the performance of the elderly in the ACS behavioral test. The electrophysiological data demonstrate, for the elderly with normality in the BAEP-click, the similar latencies between the ears, except in wave III, which indicated smaller values in the right ear. The same occurs in the altered group, but in the V wave. It is important to note that subjects have presence of all waves of the BAEP-click in the right ear and a large number of absence in the left ear. When comparing the FFR-speech variables (latency, amplitude, slope, and interpeak) according to the results of the BAEP-click, no major differences were found between the normal and altered elderly. This demonstrates that the change in the click did not influence FFR-speech performance. The data allow concluding that it was possible to generate reference values for the different behavioral tests. As well as, sensorineural hearing loss influences the results of the Adapted Compressed Speech Test, in order to suggest that it is not applied in the elderly with peripheral alteration. Regarding schooling and cognition, there is similarity between the elderly with normal hearing thresholds and hearing loss of mild or moderate degree. There weren't differences between the ears in the BAEP-click, and the reference values for FFR-speech were determined.